Um olhar sobre o patrimônio cultural: proposta da inclusão da educação patrimonial no currículo do curso de pedagogia da Universidade Estadual de Goiás - Silva, Vágnar Gonçalves da (2007)
Brasil presents a big diversity of cultural mixes. It´s a multicultural country, and it needs to preserve, bring back and increase the value of this diversity. But for what it happens it needs develop the sensibility and the conscience of all people and this sense has to be started since the childhoods or better, this sense has to be developed on children education. But the masters (teachers) which work with this sense are prepared to work with this point (thema)? With this objective that we developed this search, studying Matriz curricular do Curso de Pedagogia da Universidade Estadual de Goiás using questions to pupils and masters (teachers) for we get an idea of how this point is debated by people that are and will be reponsibles by education of our children.